Carcass Characteristics And Physiological Status Of Nutrients Carcass Characteristics And Physiological Status Of Nutrients Including Heavy Metal And Pesticide Residues In Selected Beef esticide Residues In Selected Beef Wholesale Cuts Of Indian Zebu Cat - Chakraborty, A.; Biswas, S.; Chakraborty, R.; (Chakraborty), A. Dhargupta; Majumder, D. (Journal of Meat Science, 2014)
A study was carried out to assess the carcass characteristics, proximate composition, fatty acid profile, essential macro and micro-elements as well as the levels of some heavy metals and pesticide residues in some wholesale cutup parts (round, loin, flank and chuck) of pasture-fed Indian zebu cattle after collecting samples from the Tangra slaughter house, Kolkata, India. The carcass characters, weight of the wholesale cuts and plucks were having agreement with the standard values. Significant (P
Keywords: carcass characters; nutrients; heavy metals; pesticides in beef